2008
DOI: 10.1108/14637150810888037
|View full text |Cite
|
Sign up to set email alerts
|

Business process management in a Brazilian public research centre

Abstract: Purpose – The purpose of this paper is to analyse how a Brazilian public research centre implemented business process management (BPM) highlighting the challenges of change that have to be dealt with in the stage developed by this organisation. Design/methodology/approach – The first author of this paper accompanied the implementation of BPM in the research centre for 33 months in order to analyse documents and reports and have interviews with various managers and employees. Findings – The studied organisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 10 publications
0
2
0
5
Order By: Relevance
“…Some authors focus their studies on the relationship between organizational culture and business process management in the context of culture as the main success or failure factor in implementation of business process reengineering or BPM initiatives in organizations (Grau and Moormann 2013). For example, O. F. Sentanin et al demonstrated in their research that the organizational culture, which dominates public organizations even after the BPM is implemented, has a major effect on traditional functional thinking (Sentanin et al 2008). They showed that a change of culture, which is reflected in personnel behavior, is a success factor in implementation of the process approach, but it also affects achieving process maturity in an organization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some authors focus their studies on the relationship between organizational culture and business process management in the context of culture as the main success or failure factor in implementation of business process reengineering or BPM initiatives in organizations (Grau and Moormann 2013). For example, O. F. Sentanin et al demonstrated in their research that the organizational culture, which dominates public organizations even after the BPM is implemented, has a major effect on traditional functional thinking (Sentanin et al 2008). They showed that a change of culture, which is reflected in personnel behavior, is a success factor in implementation of the process approach, but it also affects achieving process maturity in an organization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Other authors describe these capacities as BPR team competencies which in their view include knowledge and skill regarding the organisational functional process, BPR and BPR methodologies, change management, role of IT in BPR and BPR project management. These are seen as critical for organisational BPR project success (Thong et al, 2000;McAdam and Corrigan, 2001;Scholl, 2005). Hence, it becomes necessary for firms to emphasise retention of the reengineering team until completion, as the reengineering team"s competence is pertinent in change management, the role of IT in BPR and those functions of the organisation to be redesigned; empowering employees; and continuously monitoring and improving the BPR outcome (Thong et al, 2000).…”
Section: Theoretical Expositionmentioning
confidence: 99%
“…Tais processos são efetivados de modo contínuo pelo pessoal que faz parte da sua força de trabalho. Desse modo, se os processos são gerenciados com êxito pelos membros da organização, podem contribuir para alcançar a estratégia da empresa e melhorar a gestão dos processos principais, que agregam valor ao cliente (SENTANIN;CÉSAR;JABBOUR, 2008 Entender como estão as práticas de Gestão de Processos por meio das contribuições do GesPública tende a trazer vantagens. Roczanski (2009, p. 4…”
Section: Introductionunclassified